Expressions of Melancholy : aspects of the collection 6. - Brandtzaeg, Karl J. (Oslo : National Museum of Contemporary Art Oslo, 2003)
Abramovic, Marina ; Baird, Vanessa ; Bakken Sorensen, Brit ; Benat, Laetitia ; Bendik Sjur, Arne ; Bleken, Hakon ; Bolling, Svein ; Cronqvist, Lena ; Dürer, Albrecht ; Goldin, Nan ; Nondal, Astrid ; Nyborg, Hege ; Ransve, Bjorn ; Semper, Ene-Liis ; Serck-Hanssen, Fin ; Sherman, Cindy ; Sontag, Susan ; Svalheim, Hilde ; Vikhagen, Havard
Engels
Noors
Exhibition. Expressions of Melancholy : aspects of the collection 6. National Museum of Contemporary Art Oslo, 05.06.2003 - 28.09.2003.
boek